Interactions between HQ and Divisions in a MNC - Some Consequences of IT Implementation on Organizing supply Activities - Svend Ole Madsen; Ole Stegmann Mikkelsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
This article focuses partly on the interaction between a company headquarter and the divisions and partly on how new IT technologies can influence this process. Specifically, the influence of a newly developed Data Warehouse sys-tem organization of supply is investigated. Based on earlier perspectives, such as core competence and portfolio perspectives, the interactions are examined, and a third perspective, in which elements of the two are coordinated and inte-grated, is introduced. Based on a single case study of Danfoss A/S, the new IT opportunities are then used to illustrate the implications on the organisation of purchasing activities.
Keywords: 330; Strategic purchasing; multinational companies (MNCs); Informa-tion; Communication and Technology (ICT); organisational development; Multinationales Unternehmen; Informationstechnik; Organisationsstruktur; Kommunikation; Dänemark